IT'S A WONDERFUL WORLD : How to protect the planet and change the future - French, Jess; Nandhra, Aleesha (London : Dorling Kindersley, 2022)
This book teaches kids about the importance of diversity of plants, animals, and environments, and how to protect these wonderful and crucial elements of our world.
Includes index.
Keywords: Animals -- Juvenile literature; Animal ecology -- Juvenile literature; Plants -- Juvenile literature; Plant ecology -- Juvenile literature; Environmental protection -- Juvenile literature